PERANCANGAN APPLICATION PROGRAMMING INTERFACE PADA WEBSITE SAHEB MENGGUNAKAN ARSITEKTUR REST - Sanjaya, Vic Bradley; Rahman, Syaiful; Surasa, Hendra (STMIK KHARISMA Makassar, 2025)
Saheb is a web-based pet shop application built with Next.js and Firebase, offering pet product sales and online veterinary consultation services. However, Saheb faces challenges in integrating with third-party applications and system efficiency due to its reliance on Firebase. This study aims to design a REST API using Express.js to enhance modularity, integration, and application performance. The research methodology includes literature review, REST API design using layered architecture principles, and JWT authentication implementation. Evaluation shows that the REST API implementation reduced Firebase resource usage by 57.66% and significantly improved website performance, with average reductions in Speed Index, TBT, and LCP times. The integration of the REST API with third-party applications successfully facilitates interaction without direct Firebase connections. The study concludes that the implementation of REST API improves the efficiency, scalability, and performance of the Saheb application, and opens up opportunities for further development.